The native brotherhoods modern intertribal organizations on the Northwest coast - Drucker, Philip 1911-1982 (Washington United States Government Printing Office, 1958)
A study of the Alaska Native Brotherhood and the Native Brotherhood of British Columbia. Appendices include constitutions of the two societies.
Also issued as House document no. 39, 85th Congress, 1st session.
With : Archeological investigations at the mouth of the Amazon / Meggers, Betty Jane. Washington : G.P.O., 1957. Bound together subsequent to publication.
Includes bibliographical references (pages 161-164) and index.
Keywords: Alaska Native Brotherhood; Native Brotherhood of British Columbia; Indians of North America -- Northwest Coast of North America; Acculturation; Indians of North America -- Cultural assimilation -- Alaska; Indians of North America -- Cultural assimilation -- British Columbia